PERSEPSI MAHASISWA UNIVERSITAS RIAU TERHADAP PELAKSANAAN PIDANA POKOK DAN PIDANA TAMBAHAN MENURUT UU NO 31 TAHUN 1999 TENTANG TINDAK PIDANA KORUPSI - Abdur Razak; Hambali '; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract :This research is based on the problems that arise from the observations made by the researcher that is about the implementation of additional criminal and additional crimes under UU No. 31 of 1999 on corruption crime. Based on preliminary data obtained from the literature study is many problems in the implementation of the main criminal and additional crimes on the defendant corruption crime, for example, multitafsir rule or penalty that is still considered mild in the perpetrators of corruption crime classified as extraordinary crimes or extraordinary crimes. The formulation of the problem in this research is (1) How is the perception of student riau university to the main punishment according to UU no 31 year 1999 about corruption crime? (2) How is the perception of student of university riau toward additional criminal according to UU no 31 year 1999 about corruption crime?. The purpose of this research is to find out the perception of students of riau university on the implementation of principal criminal and additional crimes according to UU no 31 year 1999 about corruption crime. This research is descriptive qualitative method. Population in this research is student of university of riau from 9 faculty, then simplified become 3 faculty which study jurisprudence only. The sample in this study amounted to 120 people from 3 faculties. Data collection techniques used interviews, questionnaires, and literature studies. Based on the results of this research can be concluded the perception of university of riau students on implementation of basic criminal according to UU No. 31 of 1999 on corruption is good. Nevertheless, the perspective of university of riau students on the additional criminal implementation according to UU No. 31 of 1999 on corruption crime is not good.Keyword : Perception, Students, additional crime